Perancangan dan Implementasi Strategi Pemasaran Digital Pada UMKM Harum Bakery - Angie Angie; Renza Fahlevi; Fitriana Aidnilla Sinambela (Pusat Riset dan Inovasi Nasional, 2023)
The aim of implementing this service program is to help solve the problems faced by MSMES in Batam City, especially in digital marketing. The MSMEs targeted are Harum Bakery which focuses on the bread sector. Previously, Harum Bakery's sales system was still based on a consignment system in minimarkets, markets and supermarkets. Since the beginning, Harum Bakery has only used traditional marketing methods, namely word of mouth. Therefore, in this activity the author will help design and implement digital marketing at Harum Bakery. The method used in this activity is observation and interviews with MSMEs owners. The results of this activity prove that the application of digital marketing can provide many benefits for Harum Bakery, such as increasing revenue or product sales, reaching a wider range of consumers, increasing brand awareness, and being able to compete with other competitors.